PELAYANAN UMUM DI POLRES REMBANG JAWA TENGAH UNTUK TERWUJUDNYA ZONA INTEGRITAS - Damayanti Damayanti; Rikah Rikah (J-MACC, 2022)
POLRES Rembang requires performance measurement in public services. The purpose of this study is to determine: 1). the effect of effectiveness and efficiency on public service performance, 2). the influence of officer discipline on public service performance, 3) the effect of officer initiative on public service performance, 4). the personal influence of officers on the performance of public services, 5). the influence of information systems on public service performance, 6). suggestions and expectations from the community. The research method used is quantitative with the population is the people who enjoy the services provided by POLRES Rembang. This study used a sample of 200 respondents. The sampling technique used is cluster sampling, which is the basis for the number of districts in Rembang Regency. The technique of collecting data with a questionnaire using a linkert scale. The analysis technique used is multiple linear regression. The results showed: 1). effectiveness and efficiency have a positive effect on public service performance, 2). Officer discipline has a positive effect on public service performance, 3) officer's initiative has no significant negative effect on public service performance, 4). personal officers have a positive effect on public service performance, 5). Information systems have a positive effect on public service performance, 6). the hope of the community, POLRES Rembang continues to improve the performance of its services. The test value of determination is 0.768, which means that the factors examined in the study have an influence on the performance of the POLRES Rembang service by 76.8%, while the remaining 23.2% is influenced by other factors outside the model studied.